The Brain Drain And Human Rights - Aisyah Wardatul Jannah (Faculty of Law, University of Mataram, 2018)
The terms of brain drain refers to the movement of the skilled people from less developed country to the developed country caused by several factors such as politic unstability, poverty and development problem in the source country in order to seek out for the new opportunity and better quality of life in the receiving country. Since the movement of the brain have increased year by year, it is arises more development problem to the source country in lack of health care acces, poverty continuously and even died. The study resource of this essay conduct from the library, journal and internet resources, to examine the definition and describe the impact which caused by the brain drain. As the consequences, it is resulted that the brain drain has a negative impact to the resource country but in the other hand it has positive impact as well, further it is qualified that the brain drain have a strong relation with the human rights and have arises question does this brain drain can be blamed for the development problem in source country.